Relasi Makna dalam Bahasa Serawai Dialek ‘AU’ (Sinonim, Antonim, Dan Homonim) di Desa Pasar Pino Kecamatan Pino Raya Kabupaten Bengkulu Selatan - Anggraini, Zelvia; Akbarjono, Ali; Heriadi, Meddyan (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
Serawai language is an important cultural heritage for the Serawai tribe, but its use has declined among the younger generation due to the influence of globalization. This study aims to explore and describe the form of synonym, antonym, and homonym meaning relations in the Serawai language dialect "AU" spoken in Pasar Pino Village, Pino Raya District, South Bengkulu Regency. The method used is a descriptive qualitative approach, with data collection through direct observation and interviews with members of the local indigenous community. The results of the study showed that there were 40 synonym relations, 33 antonym relations, and 30 homonym relations that provided an in-depth picture of the richness of the Serawai language vocabulary. To support language preservation, it is recommended that the community and government hold educational programs and cultural activities, such as language festivals and workshops, to raise awareness of the importance of using Serawai language among the younger generation. These findings are expected to make a significant contribution to the linguistic understanding of the Serawai language and support efforts to preserve regional languages ​​in South Bengkulu Regency.